Development of a serological based vaccine matching technique for Foot-and-Mouth Disease (FMD) SAT 2 viruses - Opperman, Pamela A. (University of Pretoria, 2024)
Dissertation (MSc (Tropical Animal Health))--University of Pretoria, 2024.